Pengaruh laba bersih, ukuran perusahaan, struktur modal, dan likuiditas terhadap harga saham - Melinda, Hesti Sisma; Dewi, Siska (LPMP Imperium, 2023)
This study aims to determine the effect of net profit, company size, capital structure, and liquidity on stock prices (a case study on a manufacturing company in the food and beverage sub-sector in 2018-2022). The research population is a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange for 2018-2022. The sampling technique used was the purposive sampling technique. The data type used is secondary data obtained from the Indonesia Stock Exchange (IDX). The data analysis method used is multiple linear regression using SPSS version 25. The partial results show that stock prices have a positive and significant effect on stock prices, company size has no effect on stock prices, capital structure has a negative and significant effect on stock prices, and liquidity has no effect on stock prices. Public statement interest This research can be used as input in assessments carried out by company management and the wider community to measure share prices to attract investors to invest their capital in the company to make a profit.